PEMANFAATAN SAMPAH ORGANIK PASAR TRADISIONAL DENGAN PENAMBAHAN KOTORAN SAPI DAN KOTORAN AYAM SEBAGAI BAHAN ENERGI ALTERNATIF BIOGAS - Ratna Dwi Praptiwi; Mohammad Mirwan (EnviroUS, 2021)
Organic waste is the waste residue of a material that has been thrown away, but its existence can still be utilized. So far, organic waste from traditional markets is directly disposed of in landfills. Even though organic waste if left uncontrol cause unpleasant odors, it can also cause environmental pollution because organic waste can be destroyed by itself so that it will absorb into the soil which can cause pollution to groundwater infiltration. Nutrients contained in traditional market waste can be combined with animal manure that is cow manure and chicken manure, so this research will produce alternative biogas energy, it can be used in daily life. The decomposition of organic matter with a fermentation process by microorganisms on the material which takes place anaerobically to produce methane. This study uses a variety of ingredients that have been determined to find the maximum concentration with the best results. The ratio variation used is the mixture of traditional market organic waste materials with cow manur (90:10, 80:20, 70:30, 60:40, 50:50) as well as the mixture of traditional market organic waste materials with chicken manure (90 : 10, 80:20, 70:30, 60:40, 50:50) respectively at the reactor volume of 6 liters with a fermentation process time of 7 days and 14 days. The parameters analyzed consisted of water content, temperature, pH, and C / N ratio. The results showed that the best biogas was obtained during fermentation for 14 days in a mixture of organic waste and cow manure at ratio of 80:20 with a water content of 90.7%, a C / N ratio of 146.4%, indicated by an increase in temperature reaches 320C also with the longest flame for 2.10 minutes and the flame indicator is blue. Key words: Organic Waste, Animal Manure, Biogas